Active Damping of Power Swings in Bulk Power Transmission Systems - Jäger, Johann; Romeis, Christian (2012 IEEE International Conference on Power System Technology (POWERCON), 2012)
This paper presents a new method to damp power swings in transmission systems. Power swings can cause damages, problems with active power delivery and so on. The number of transient stability problems will rise in the future due to restructuring of power systems by renewable energy sources. Especially systems with a high power transmission over a long distance are prone to stability problems. In such a case, power swings are also poorly damped, so effective measures have to be done to strengthen the stability of the transmission system. With an active damping procedure the stress on the power system can be minimized. In this research work, the damping effect is realized via a switching scheme for the circuit breakers, which connect the generator to the power grid. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.leen.active
Keywords: auto-reclosure; bulk power transmission; damping of power swings; power swings; reliability of power systems

Adaptive Protection Relay Coordination in Future Grids - Ideas, Approaches, and Examples - Jäger, Johann; Dauer, Maximilian; Fuchs, Jochen; Romeis, Christian (IEEE Power and Energy Society General Meeting, 2013)

Automatisierte Bewertung der Schutzsicherheit unter Berücksichtigung elektromechanischer Ausgleichsvorgänge in Hochspannungsnetzen - Meyer, Janick; Romeis, Christian; Jäger, Johann (FNN/ETG-Tutorial Schutz- und Leittechnik 2018, 2018)

Calculation of electrical Field below Hybrid Overhead Lines - Schindler, Jakob; Romeis, Christian; Jäger, Johann (PESS Power Energy Student Summit, 2015)

Digital System Protection Design – A New Toolchain For Protection System Automation - Meyer, Janick; Biller, Martin; Jäger, Johann; Dauer, Maximilian; Romeis, Christian; Krebs, Rainer; Shang-Jaeger, Li; Schäkel, Nils; Braun, Benjamin; Stumpe, Maximilian; Tünnerhoff, Philipp (CIRED 2019, International Conference on Electricity Distribution, 2019)
This paper is proposing an integrated digital toolchain for the design and parametrization of protection relays. The process flow is fully digitized and automated. It considers the grid and the protection behavior as a whole with the use of integrated grid and protection models. Thus it can be adapted highly flexible to frequent changing grid conditions. Moreover an optimization tool finds the best feasible solution of the protection system concerning the supply reliability under diverse grid conditions. A case study illustrates the functioning of that process and the results to be achieved.Future power grids are facing an increased diversity of operation and disturbance conditions. These are caused by fluctuating infeeds of renewable energy sources as well as the use of unconventional grid devices like voltage source converters or short-circuit current limiters. Maintaining a high degree of supply reliability, the protection systems and their design process have to be adapted to the changing conditions.This paper is proposing an integrated digital toolchain for the design and parametrization of protection relays. The process flow is fully digitized and automated. It considers the grid and the protection behavior as a whole with the use of integrated grid and protection models. Thus it can be adapted highly flexible to frequent changing grid conditions. Moreover an optimization tool finds the best feasible solution of the protection system concerning the supply reliability under diverse grid conditions. A case study illustrates the functioning of that process and the results to be achieve

Duale Netzplanung – Leitfaden zum netzkompatiblen Anschluss von dezentralen Energieeinspeiseanlagen - Jäger, Johann; Romeis, Christian; Petrossian, Edmond (Springer Vieweg Verlag, 2016)

Duale Netzplanung – Netzanbindung regenerativer Energieeinspeiseanlagen - Romeis, Christian; Petrossian, Edmond; Jäger, Johann (VDE-Kongress Smart Cities, 2014)

Duale Netzplanung Netzanbindung von Erneuerbare-Energie-Anlagen - Romeis, Christian; Petrossian, Edmond; Jäger, Johann (Elektrizitätswirtschaft, 2014)
UnivIS-Import:2015-04-14:Pub.2014.tech.IE.leen.dualen

Dynamic Protection Security Assessment, a Technique for Blackout Prevention - Romeis, Christian; et al. (2013 IEEE PowerTech (POWERTECH), 2013)
In most cases of blackouts, protection systems play a significant role. The maloperation of one protection system can lead to a cascade-tripping of many other protection devices, and so a wide-area interruption of the power grid can affect millions of people. Therefore one important task of a transmission system operator (TSO) is to initiate remedial measures to prevent the grid from such interruptions. The TSO has different tools to operate a secure and reliable transmission grid, e.g. state estimator, dynamic security assessment (DSA) tools and so on. The dynamic protection security assessment (DPSA) is another tool to assess the situation in the grid depending on different contingencies. In addition to the transient network models, protection system models are also included for the simulation of stability problems. In contrast to DSA, DPSA assesses the time-dependent behavior of the protection systems and shows their influence on the grid security. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.leen.dynami
Keywords: blackout prevention; dynamic protection security assessment; dynamic security assessment; protection systems; stability phenomena

Dynamic protection security assessment: influences of protection systems on the transient system security - Romeis, Christian; Eberle, Thomas; Jäger, Johann (13th International Conference on Development in Power System Protection 2016 (DPSP), 2016)
The system integrity and reliability is a major task of transmission system operators (TSOs). Different tools are available to drive a secure power system. But most of them missed the assessment of the influences of protection systems on the system security. Therefore we introduced the Dynamic Protection Security Assessment (DPSA). Protection systems like distance protection relays were included in transient stability analyses. The impact of these were analysed based on different indices which assessed the number of unwanted operation, number of pickups and the amount of undesired lost load. By taking several contingencies into account, the DPSA gave a ranking of critical relays which were susceptible to unwanted operation during transient stability simulations. Two case studies showed that power swing blocking is a suitable measure to prevent the system from blackouts, but it was not always useful. Especially during loss of synchronism of one generator or a coherent group, a dedicated system split prevented the grid from total blackout.

Dynamische Schutzsimulation zur vorausschauenden Netzausfallvermeidung - Romeis, Christian; Jäger, Johann (7. ETG/FNN Tutorial "Schutz- und Leittechnik", 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.leen.dynami

Induced Voltages on HVDC Systems at the Same Support Structure due to Capacitive and Inductive Coupling - Romeis, Christian; Jäger, Johann; Luther, Matthias, Kristian Steckler; Keil, Timo (IET-ACDC Conference on AC and DC Power Transmission, 2015)

Influence of Ion Current on Current Transformes of AC Systems in Near Vicinity of DC Systems - Romeis, Christian; Jäger, Johann, Kristian Steckler; Keil, Timo (2015 IEEE Eindhoven PowerTech, 2015)
Equipping one support structure with DC and AC systems in parallel can increase the transport capacity of existing transmission corridors. The constant electric field of the DC system induces a constant DC component into the AC systems in near vicinity. All magnetic equipment including an iron core is in danger to saturate. Especially current transformers (CTs) for protection issues can be influenced in the way that the time-to-saturation is reduced. Therefore, maybe the protection relays are affected adversely and the selectivity is harmed. This paper evaluates this major impact by determining the transient dimensioning factor and the time-to-saturation in presence of a constant DC component in the fault current and remanent flux. The influence on the transient dimensioning factor is marginal and can be almost neglected. But for metering cores it could be a problem and should be tested because of the different excitation curve

Innovative Strategies for Protection Security Assessment - Romeis, Christian; Fuchs, Jochen; Jäger, Johann; Krebs, Rainer (Power and Energy Society General Meeting 2011, 2011)
Protection security assessment of power grids is getting an important task in the course of a decarbonized power generation and a competitive energy business. The analysis of past blackouts studied by the North American Electric Reliability Council (NERC) shows that protection relays are involved in about 75% of all major disturbances. Protection security assessment can be investigated under two different aspects: on the one hand the behavior regarding selectivity, speed and sensitivity and on the other hand the behavior regarding the response on dynamic network phenomena as voltage stability and transient stability. This paper is focused on the protection response on dynamic network phenomena and presents innovative strategies for this investigation aspect. Applicable protection models and the simulation environment based on PSS®NETOMAC will be described. Case studies on real networks show the way of investigation and the achieved improvement of dynamic protection security based on the applied innovative strategies. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.leen.innova
Keywords: blinder characteristic; dynamic protection simulation; generic protection models; major disturbances; power swing; Protection security assessment; zone settings

Intelligent prosumer coupling by two galvanically isolated battery storage systems - Graber, Thomas; Romeis, Christian; Petrossian, Edmond; Jäger, Johann (IET Electric Power Applications, 2017)

Network Planning Approach with respect to an Effective Integration of Superconduction Calbe Lines in Distribution Grids - Romeis, Christian; Jäger, Johann; Petrossian, Edmond (CIRED, International Conference on Electricity Distribution, 2015)

Protection System Reliability in the presence of HVDC and AC Transmission Systems at the same Support Structure - Romeis, Christian; Jäger, Johann; Luther, Matthias, Kristian Steckler; Reisbeck, Jörg; Keil, Timo (IEEE Power and Energy Society Gerneral Meeting, 14PESGM2702, 2014)

Real Time Adaption of Dead Time for Single Phase Auto-Reclosing - Vogelsang, Jakob; Romeis, Christian; Jäger, Johann (IEEE Transactions on Power Delivery, 2016)

Schutzanforderungen beim Betrieb einer AC/DC-Hybridtrasse - Romeis, Christian; Jäger, Johann; Butterer, Christoph; Reisbeck, Jörg (9. ETG-/FNN-Tutorial Schutz- und Leittechnik, 2016)

Secondary Arc Current During DC Auto Reclosing in Multisectional AC/DC Hybrid Lines - Schindler, Jakob; Romeis, Christian; Jäger, Johann (IEEE Transactions on Power Delivery, 2017)

Secondary Arc Current During DC Auto Reclosing in Multisectional AC/DC Hybrid Lines - Schindler, Jakob; Romeis, Christian; Jäger, Johann (2018 IEEE POWER & ENERGY SOCIETY GENERAL MEETING (PESGM), 2018)
CRIS-Team WoS Importer:2019-02-22

Use of Petri-Nets to Describe and Verify Protection System Models for Time Domain Simulations - Romeis, Christian; Biller, Martin; Jäger, Johann (2014 IET The 12th International Conference on Developments in Power System Protection (DPSP), 2014)
The assessment of critical system states via intensive power system simulation is more and more common especially for stability studies. The Dynamic Security Assessment (DSA) is one way to investigate the stability of a power system by simulating different contingencies. But one is mostly missing, the models for secondary equipment. To integrate protection systems in the simulation environment, the models have to be verified and tested, if they behave like the original relay or algorithm. Petri nets are one possibility to describe the discrete-event behaviour of protection relays like pickup, trip and reset. The Petri net model can be as detailed as needed to check the behaviour of the simulation model. This article describes different Petri nets, which include also special functionalities like power swing blocking.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.leen.useofp
Keywords: Discrete-event behaviour; Petri nets; Power system studies; Protection system models; Time domain simulation

Versorgungszuverlässigkeit erfordert Anlagenerneuerung - Ganzheitliche Methode mit hohem Einsparpotential - Romeis, Christian; Petrossian, Edmond; Jäger, Johann (EW Magazin für die Energiewirtschaft, 2014)

Versorgungszuverlässigkeit erfordert Erneuerung von Altanlagen - Ganzheitliche Planungsmethode zur Netzertüchtigung. - Petrossian, Edmond; Jäger, Johann; Romeis, Christian (Elektrizitätswirtschaft, 2014)
UnivIS-Import:2015-04-14:Pub.2014.tech.IE.leen.versor